2014
DOI: 10.1111/jan.12456
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students' prosocial motivation: does it predict professional commitment and involvement in the job?

Abstract: The results indicated that prosocial motivation is important in identifying with the profession but not necessarily for personal involvement in the job. The study gives important knowledge on how a commonly reported motivation for entering nursing relates to the nurses' attitudes about their work life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 71 publications
4
50
1
5
Order By: Relevance
“…In this respect, Ben Natan and Becker (2010) found a positive correlation between the perception of nursing and the decision of students to choose a nursing career. Moreover, Nesje (2014) reported that great social motivation for choosing nursing profession has been related to higher career commitment after graduation.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, Ben Natan and Becker (2010) found a positive correlation between the perception of nursing and the decision of students to choose a nursing career. Moreover, Nesje (2014) reported that great social motivation for choosing nursing profession has been related to higher career commitment after graduation.…”
Section: Discussionmentioning
confidence: 99%
“…the knowledge-based economy era, an organization could overcome challenges by rapid self-adaptation. Nesje (2015) explained that effective environmental education could foster the environmental knowledge management and rapid innovation in an organization and enhance the organizational members' constant learning and environmental professional development (Stéger, 2014). Gurung & Landrum (2012) mentioned that the environmental education in an organization, in the knowledge-based economy era, could achieve effective environmental knowledge management to further enhance the intangible assets of the organization.…”
Section: Professional Performancementioning
confidence: 99%
“…Colomeischia & Colomeischia (2014) covered the selection, acquisition, learning, creation, expansion, construction, and storage of knowledge in knowledge management to form the knowledge management system and further form the managerial culture system. Nesje (2015) defined knowledge management as planning, organizing, and classifying existing knowledge in an organization; such existing knowledge was "explicit knowledge", containing documentary data, work division details, traditional paper-based or electronic work records, manuals, reports, pictures, programs, images, and sound of the organization, which could effectively manage explicit knowledge from inside or outside the organization by setting up electronic database to transform knowledge into specific symbols for the systematic, handy, and clear understanding and application of the…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have widely discussed the organizational commitment of professional jobs, particularly of accountants (e.g., Lander, Koene, & Linssen, 2013;Singh & Gupta, 2015;Chong & Monroe, 2015;Sejjaaka & Kaawaase, 2014;Olsen, Sverdrup, Nesheim, & Kalleberg, 2016;Welsch & LaVan, 1981;Aranya & Ferris, 1984;Morrow & Wirth;1989;Aranya & Amernic, 1981;Reed, Kratchman, & Strawser, 1994;Ketchand & Strawser, 1998), nurses and hospital employees (e.g., Li, Early, Mahrer, Klaristenfeld, & Gold, 2014;Top, Akdere, & Tarcan, 2015;Fu & Deshpande, 2014;Yang, Liu, Chen, & Pan, 2014;Lisdiyono & Asyhar Assalmani, 2017;Laschinger, Nosko, Wilk, & Finegan, 2014;Nesje, 2015;Sharma & Dhar, 2016;Veličković et al, 2014;Yang, Liu, Huang, & Zhu, 2013;Blau, 1999;Mosadeghrad, Ferlie, & Rosenberg, 2008;Lum, Kervin, Clark, Reid, & Sirola, 1998;Ingersoll, Olsan, Drew-Cates, DeVinney, & Davies, 2002;Kuokkanen, Leino-Kilpi, & Katajisto, 2003;Lu, Lin, Wu, Hsieh, & Chang, 2002), lawyers (e.g., Wallace, 1995a;Lu, Liang, & Li, 2014), and teachers (Nart & Batur, 2014;Bogler & Somech, 2004). However, these studies only discussed the commitment of a particular professional job.…”
Section: Introductionmentioning
confidence: 99%